Liposomal Elongation Factor-1α Triggers Effector CD4 and CD8 T Cells for Induction of Long-Lasting Protective Immunity against Visceral Leishmaniasis - Sabur, Abdus; Bhowmick, Sudipta; Chhajer, Rudra; Ejazi, Sarfaraz Ahmad; Didwania, Nicky; Asad, Mohammad; Bhattacharyya, Anirban; Sinha, Utsa; Ali, Nahid (Frontiers in Immunology, 2018)
Despite advances, identification and formulation of safe and effective vaccine for long lasting protection against leishmaniasis is still inadequate. In this study we have identified a novel antigen, leishmanial EF1-α as an immuno-dominant component of solubilized leishmanial membrane antigens (SLA) that reacts with visceral leishmaniasis (VL) sera and induces cellular proliferative and cytokine response in PBMCs of cured VL subjects. Leishmanial EF1-α is a 50 kDa antigen that plays a crucial role in pathogen survival by regulating oxidative burst in the host phagocytes. Previously, immunodominant truncated forms of EF1-α from different species of Leishmania have been reported. Formulation of the Leishmania donovani 36 kDa truncated as well as the cloned recombinant EF1-α in cationic liposomes induce strong resistance to parasitic burden in liver and spleen of BALB/c mice through induction of a DTH and a IL10 and TGF-β suppressed mixed Th1/Th2 cytokine responses. Multiparametric analysis of splenocytes for generation of antigen specific IFN-γ, IL2 and TNF-α producing lymphocytes indicate that cationic liposome facilitates expansion of both CD4+ as well as CD8+ memory and effector T cells. Liposomal EF1-α is a novel and potent vaccine formulation against VL that imparts long term protective responses. Moreover, the flexibility of this formulation opens up the scope to combine additional adjuvants and epitope selected antigens for use in other disease forms also.